RELEVANSI FILSAFAT ILMU HUKUM DALAM PEMBENTUKAN METODE PENELITIAN HUKUM (SUATU TINJAUAN TERHADAP PENGARUH KONSEP FILOSOFIS DALAM PENGEMBANGAN PENELITIAN HUKUM KONTEMPORER) - Dyah Rosiana Puspitasari; Basto Daeng Robo (Khairun Law Journal, 2024)
Philosophy of law provides a deep theoretical foundation, while legal research methods provide the conceptual and technical tools needed to explore a deeper understanding of legal phenomena.Â  The importance of exploring this linkage is especially evident in the increasingly complex and dynamic era of contemporary legal research. In facing the challenges of legal complexity, researchers need a strong philosophical outlook to guide their approach in designing and conducting research. This research aims to outline the philosophical concepts in the philosophy of law that provide the theoretical basis for the formation of legal research methods and outline the main challenges faced by researchers in the integration of philosophical concepts in the development of legal research methods and how to overcome them. This research will use the type of normative research, with a conceptual approach method, using a literature review related to the philosophy of law, legal research methods, and the contribution of philosophical concepts in legal research. The data sources used, secondary data sources in the form of philosophy of law books, the main object of this research are contemporary legal research documents. The philosophy of law provides a philosophical foundation for legal science and after the birth of legal theory as an independent discipline, legal philosophy also becomes the philosophical foundation of legal theory. In legal research methods, legal ontology helps determine the scope of the research, map the body of law to be studied, and determine the relationship between elements in the research context. This process involves critical reflection and analysis to find meanings that may be hidden, then determine the value of the reality. The integration of philosophical concepts in the development of legal research methods presents significant challenges. Some of the main challenges involve the complexity and abstraction of philosophical concepts, the gap between legal research theory and practice, the heterogeneity of interpretations, and ethical dilemmas.